Classification of Precambrian Shield Lakes Based on Factors Controlling Biological Activity - Conroy, Nels (My University, 1971)
During the summer of 1970 a study was initiated to define factors controlling the biosphere in the lentic environment of the Precambrian Shield. Data were collected from nine lakes of varying size and depth located in a number of geological formations. Chemical, physical and biological conditions in these lakes were investigated at two sampling periods and the lakes were classified on the basis of morphology (surface area to volume area) and lithology (surficial and bedrock geology). Attempts were made to determine the influence of morphology and lithology on the chemical and biological conditions observed. Emphasis was placed on the relationships of these factors to aspects of the primary and secondary trophic levels in the lentic ecosystem including primary productivity and the standing crop and diversity of phytoplankton and zooplankton.
The atmosphere, a third potential factor influencing lakes was investigated by means of a network of air monitoring stations (collecting both precipitation and 'dry fallout') located throughout the greater Sudbury area.
The results of the study indicated that: 1. the lentic ecosystem in the Precambrian Shield area studied can be defined by simple chemical and physical variables. 2. the morphology of the lake basins (surface area to volume ratio) modified by lithology (primarily the presence or absence of limestone) is the major factor influencing biological activity. Lakes with a low surface area to volume ratio showed low productivity while lakes with a high surface area to volume ratio showed nigh productivity. Silica and calcium concentrations (influenced by the lithosphere) were important since relatively small changes in the concentration of these chemical species stimulated a response in the biosphere. 3. some of the lakes were affected by concentrations of sulphates conveyed to the water by the atmosphere. Observed effects included increases in the hydrogen ion concentration in lakes with low calcium concentrations (poorly buffered) and a depression of the diversity of both primary and secondary trophic levels.
Keywords: lentic, environment, Precambrian, shield, morphology, classified, lakes